Failure of noninvasive prediction of pulmonary hypertension in patients with idiopathic pulmonary fibrosis - Salajka, F; Bartos, V; Novosad, J; St'ásek, J; Bis, J; Brtko, M; Polanský, P; Koblízek, V; Sedlák, V (Monaldi archives for chest disease, 2011)
BACKGROUND: Pulmonary hypertension (PH) in patients with advanced idiopathic pulmonary fibrosis (IPF) is a complication connected with unfavorable prognosis. Great efforts have been made in attempting to establish a reliable non-invasive method which would enable detection of this complication. In this context a formula using pulmonary function parameters was published with outstanding results. METHODS: We tested the formula in 27 IPF patients who underwent a lung function examination, cardiac ultrasonography and catheterisation on the same day. RESULTS: Pulmonary hypertension was detected by catheterisation in 17 patients (63%). In our group, contrary to the published data, the aforementioned formula was neither useful for detecting patients with a high probability of PH nor as a means of calculating the mean pulmonary artery pressure in individual patients (p = 0.502 and p = 0.833, respectively). Ultrasound examination reached borderline correlation with the values measured by catheterisation when we compare patients with relevant results (r = 0.531, p = 0.051). However, the examination gave no usable results in 13 patients (48%). CONCLUSION: Our data suggests that no reliable, noninvasive method is currently available for detecting and confirming PH in IPF patients. We did not confirm the usefulness of the published formula. Further carefully organised studies will be necessary to verify or refute it.
Keywords: Female; Hypertension, Pulmonary; ultrasonografie; ženské pohlaví; Pulmonary Fibrosis; Cardiac Catheterization; Reproducibility of Results; lidé; Sensitivity and Specificity; Ultrasonography; senzitivita a specificita; prognóza; plicní fibróza; reprodukovatelnost výsledků; prospektivní studie; Male; Aged; Prospective Studies; Prognosis; plicní hypertenze; srdeční katetrizace; lidé středního věku; Respiratory Function Tests; senioři; mužské pohlaví; respirační funkční testy; Middle Aged; Humans